Study the Elastic Parameters of Sandy Conglomerate under Different Burial History and Petrophysical Modeling. (15th February 2023) - Wang, Bin; Pan, Jianguo; Huang, Yu; Wang, Guodong; Qu, Yongqiang; Zhao, Jianguo
Abstract : Over the past few years, significant exploration breakthroughs have been made in the sandy conglomerates reservoir of the Triassic Baikouquan Formation in the Mahu Sag, Junggar Basin, China. However, the elasticity and pore characteristics of the tight sandy conglomerates reservoir in this area are still unclear. Through a systematic sonic testing program of the sandy conglomerates sample collected from the Mahu Sag, the regularity behind the variation of the elasticity and pore characteristics of the sample has been analyzed and captured. The Triassic Baikouquan Formation of the slope of Mahu Sag has been through complex burial and diagenetic history. The compaction, cementation, and dissolution are the three types of diagenesis that have the greatest impact on pore characteristics in the study area. In order to quantitatively describe the influence of this complex burial and diagenetic history, we present a rock-physics modeling approach to describe the elastic properties of sandy conglomerate sample. The overall strategy of the modeling is to combine the contact cement theory (CCT), differential effective medium (DEM) and the upper Hashin-Shtrikman bound. The CCT model can well describe the history of cementation, DEM model is suitable for the history of dissolution, and HS upper bound is used to describe the history of compaction. Then, the model is used to describe well log data from sandy conglomerates reservoirs in Mahu Sag and successfully explain the rock porosity, pore shape trends, and the elasticity in the sandy conglomerate reservoirs.